2015
DOI: 10.1155/2015/986324
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Production, and Characterization of Thermotolerant Xylanase from Solvent TolerantBacillus vallismortisRSPP-15

Abstract: Sixty bacterial strains isolated from the soils sample in the presence of organic solvent were screened for xylanase production. Among them, strain RSPP-15 showed the highest xylanase activity which was identified asBacillus vallismortis. The isolate showed maximum xylanase production (3768 U/mL) in the presence of birch wood xylan and beef extract at 55°C pH 7.0 within 48 h of incubation. The enzyme activity and stability were increased 181.5, 153.7, 147.2, 133.6, and 127.9% and 138.2, 119.3, 113.9, 109, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
4
4
0
1
Order By: Relevance
“…Literature reports from previous studies reveal that the incubation time for optimal cellulase production by other Streptomyces species were in the range of 72-196 h [28,47,56,57]. Nevertheless, the findings of this study agree with that of other authors who reported 48 h as optimum for xylanase production [58][59][60]. However, most other studies recorded longer optimum incubation time for both cellulase and xylanase production using different substrates [27,36,45,61].…”
Section: Time Course and Kinetics For Production Of Cellulase And Xylsupporting
confidence: 81%
“…Literature reports from previous studies reveal that the incubation time for optimal cellulase production by other Streptomyces species were in the range of 72-196 h [28,47,56,57]. Nevertheless, the findings of this study agree with that of other authors who reported 48 h as optimum for xylanase production [58][59][60]. However, most other studies recorded longer optimum incubation time for both cellulase and xylanase production using different substrates [27,36,45,61].…”
Section: Time Course and Kinetics For Production Of Cellulase And Xylsupporting
confidence: 81%
“…Similar findings with this study for the optimal initial pH 7 for xylanase production have been reported in previous studies on Bacillus species, including B. pumilus ASH, Bacillus altitudinis DHN8, B. amyloliquefaciens XR44A and B. vallismortis RSPP-15 (Sanghi et al, 2008;Adhyaru et al, 2014;Amore et al, 2013;Gaur et al, 2015). Contrary to this result however, optimal initial pH varied for xylanase production by B. megaterium (pH 7.5), B. subtilis (pH 8) and B. pumilus VLK-1 (pH 6), (Tandon and Sharma, 2014;.…”
Section: Effect Of Initial Ph On Holocellulase Productionsupporting
confidence: 91%
“…The biggest challenge in conversion of biomass with hyperaccumulated contaminants into fermentable sugars is the inhibition of hydrolytic enzymes by absorbed metal contaminants [ 7 ]. Because of the complexity of dry biomass and presence of metal contaminants, it is difficult to hydrolyze a hyperaccumulator efficiently with a single enzyme system [ 8 , 9 ]. Therefore application of a crude enzyme cocktail may be an efficient strategy to hydrolyze metal-contaminated biomass [ 10 ].…”
Section: Introductionmentioning
confidence: 99%